Efektivitas Thumb Spica Splint Modifikasi terhadap Penurunan Nyeri Ibu Jari pada Pemain Bulutangkis di Kabupaten Karanganyar - Alfan Zubaidi; Muh. Syaiful Akbar; Sisy Bania; Anissa Eka Septiani (Journal Research of Health Administration and Public Health (JRHAPH), 2026)
Thumb joint pain caused by overuse injury is one of the most common musculoskeletal complaints among badminton players and may impair racket grip strength and overall athletic performance. The use of a thumb spica splint is a conservative intervention designed to stabilize the carpometacarpal (CMC) joint and reduce pain. This study aimed to evaluate the effectiveness of a modified thumb spica splint in reducing thumb joint pain among badminton players in Karanganyar Regency. A quasi experimental study with a post-test-only control group design was conducted. A total of 100 participants were allocated into two groups: a control group (n = 50) using a standard thumb spica splint and an intervention group (n = 50) using a modified thumb spica splint. Pain intensity was assessed using the Visual Analog Scale (VAS). Data analysis included descriptive statistics, the Shapiro–Wilk normality test, and the Mann-Whitney U test, with a significance level of p < 0.05. The results showed that the mean VAS score was 4.50 ± 0.51 in the control group and 1.84 ± 0.42 in the intervention group. The Mann-Whitney U test demonstrated a statistically significant difference between the two groups (p < 0.001), with a 59.1% greater reduction in pain scores among participants using the modified thumb spica splint. These findings indicate that the modified thumb spica splint is more effective than the standard thumb spica splint in reducing thumb joint pain among badminton players. The modified orthosis has the potential to serve as an evidence-based conservative intervention for managing pain associated with overuse injuries while supporting improved hand function in badminton athletes.